IMPROVEMENT OF THE ASSESSMENT OF COMPANIES' CREDIT WORTHINESS AS A PRIORITY DIRECTION OF LENDING THEIR FOREIGN TRADE ACTIVITIES (American Journal of Business Management, Economics and Banking, 2025)
Improving the assessment of companies' creditworthiness is a prerequisite for increasing the level of availability of commercial bank loans provided to finance their foreign trade activities. In addition, it is one of the main methods for reducing credit risk for commercial banks. The article provides a comparative analysis of methods for assessing the creditworthiness of companies, identifying their advantages and disadvantages. Also, the article develops scientific proposals aimed at improving the practice of assessing companies in banks of Uzbekistan.